Jejak Pemikiran Abu Mansur Al Maturidi dan Abu Lais Al-Samarqandi tentang Keimanan - Farkhan Fuady; Nur Alfianti (Program Studi Aqidah dan Filsafat Islam, 2021)
Faith is the main foundation for every Muslim. In the world of Islamic thought, there are many figures who review faith. Among these figures are Abu Mansur Al Maturidi and Abu Lais Al Samarqandi. Of the two figures, there is a book by Abu Lais entitled Bahjatul 'Ulum Fi al-Syarh bi Bayani Aqidah al-Usul which discusses the concept of faith. The study used qualitative methods, with a literature review approach. Philological studies are also used to study a manuscript or book written in the past. Sources of research data are obtained from books, scientific articles, and trusted websites. In this study, it was found several points about the concept of faith of the two figures, namely the concept of faith of these two figures were equally influenced by the Imam Hanafi or Hanafiah schools but in the elaboration of the concept of faith Abu Mansur Al Maturidi tends to use logic while Abu Lais Al Samarqandi tends to textual provisions. So in this study found differences and similarities about the concept of faith of the two figures.AbstrakKeimanan merupakan fondasi utama bagi setiap muslim. Dalam dunia pemikiran Islam, terdapat banyak tokoh yang mengulas tentang keimanan. Diantara tokoh tersebut adalah Abu Mansur Al Maturidi dan Abu Lais Al Samarqandi. Dari kedua tokoh tersebut terdapat kitab karya Abu Lais yang berjudul Bahjatul ‘Ulum Fi al-Syarh bi Bayani Aqidah al-Usul yang membahas konsep keimanan. Penelitian ini menggunakan metode kualitatif, dengan pendekatan literature review. Kajian filologi juga digunakan untuk mengkaji suatu manuskrip atau kitab yang ditulis dimasa lampau. Sumber data penelitian didapatkan dari buku, artikel ilmiah, maupun website yang terpercaya. Dalam penelitian ini ditemukan beberapa poin tentang konsep keimanan dari kedua tokoh, yaitu konsep keimanan yang sama-sama dipengaruhi oleh madzhab Imam Hanafi atau hanafiah, namun dalam penjabaran mengenai konsep keimanan Abu Mansur Al Maturidi cenderung menggunakan logika sedangkan Abu Lais Al Samarqandi cenderung pada ketetapan nash. Sehingga dalam penelitian ini ditemukan perbedaan dan persamaan tentang konsep keimanan dari kedua tokoh tersebut.